Meningkatkan Aktivitas, Motivasi Belajar Dan Hasil Belajar Peserta Didik Menggunakan Kombinasi Model Picture And Picture, Group Investigation Dan Numbered Heads Together - Taufik Hidayat; Sulaiman (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this study is the low motivation, activity, and learning outcomes of natural sciences due to the lack of active involvement of students in the learning process, students do not understand the concept of learning, and are less enthusiastic. The purpose of this study was to describe teacher activity, student activity, learning motivation and student learning outcomes in learning by using the picture and picture, group investigation and numbered heads together learning models. This study used Classroom Action Research (PTK) which was held in four meetings with fifth grade students at SDN 1 Bajuin, a total of 20 students consisting of 9 male students and 11 female students, in the even semester of the 2021/2022 academic year. The results of the study showed that at the fourth meeting: teacher activity scored 32 with very good criteria, student activity was 100% active, students who were motivated to learn were 96.67%. The learning outcomes of classical students reach a level of 100%.